Collaborative Learning Strategies in Improving High School Students' Chemistry Literacy: A Systematic Literature Review - Nadila Cempaka Hany; Dyah Purwaningsih (Universitas Pendidikan Ganesha, 2025)
Technological developments are driving education in Indonesia to master 21st-century skills, including the 4Cs. This study aims to identify collaborative learning strategies to improve chemical literacy through a systematic literature review (SLR) of 30 relevant journals. The analysis results indicate that weak chemical literacy is caused by student factors (lack of communication skills, participation, psychological aspects, and technical barriers) and teachers (minimal training and scaffolding). Collaborative learning has the potential to improve chemical literacy through Problem-Based Learning (PBL), Project-Based Learning (PjBL), Predict-Discuss-Explain-Observe-Discuss-Explain (PDEODE), Discovery Learning (DL), and Collaborative Problem-Based Learning (CPBL) models. In addition, ethnoscience approaches, Socio-Scientific Issues (SSI), Representations Learning, and Blended Learning also support literacy improvement. The implementation of these strategies is expected to make a real contribution to students' chemical literacy.